Composition of colostrum and milk of différent genotypes of ewes - Csapó, János; Keszthelyi, Tibor; Csapó Kiss, Zsuzsanna; Lengyel, Attila; Andrássyné Baka, Gabriella; Vargáné Visi, Éva (Acta Agraria Kaposváriensis, 1998)
Dry matter, total protein, true protein, whey protein, true whey protein, casein, NPN content, immunoglobulin-G, amino acid content, amino acid composition and biological value of protein, ash and macro- (potassium, sodium, calcium, phosphorus, magnesium) and microelement (zinc, iron, copper, manganese) content of colostrum and milk of 104 Hungarian Merino, 20 awassi, 14 langhe, 16 cigaja, 11 cikta, 12 black racka, 8 white racka, 4 karakul, 3 kent and 1 wild ewe were investigated until the 40th day of lactation. It was found that all protein fractions decreased considerably in the period of 1-2 days after lambing. After the 5th day most of the components were adjusted to a permanent level. The ratio of whey protein and true whey protein decreased considerably, and the ratio of NPN and casein increased considerably, while that of true protein showed no significant change. The concentration all of the amino acids in the colostrum and milk changed significantly after lambing. In the milk protein most of the essential amino acids decreased, while glutamic acid and proline increased; consequently the biological value of the protein in the colostrum milked directly after lambing was the highest (108.5), but this value decreased to 78-80 after the fifth day of lactation. It was established that the first milked colostrum of the twin lambing ewes contained significantly more dry matter, total protein, true protein, whey protein, true whey protein and immunoglobulin-G than that of mothers with single progeny. The biological value of protein was higher in colostrum samples from twin lambing ewes than in those in single lambing ewes. There was no significant change in the casein, NPN and macro- and microelement content between twin- and single lambing animals. Twenty-four hours after parturition no differences in colostrum composition were found with respect to any component investigated. According to our investigations the ratio of casein is higher; against this the ratio of whey protein is lower in the milk protein of Hungarian Merino, awassi, langhe, black- and white racka, than that of sarda, cigaja and cikta. Consequently the milk of the former genotypes is more suitable for cheese making, while that of milk of the latter genotypes is more suitable -due to their higher ratio of the higher biological value whey protein- for processing as liquid milk products. According to our investigations the biological value of milk protein is the same in ewes and cows, and both are lower than that of goats.
Keywords: ewe; colostrum; milk composition; protein fractions